Angioarchitecture of primary oral malignant melanomas - Lee, Y.J.; Nagai, N.; Siar, C.H.; Nakano, K.; Nagatsuka, H.; Tsujigiwa, H.; Roan, C.H.; Gunduz, M. (2002)
Angiogenesis is an essential process in the progression of malignant tumors. However, little is known of the angioarchitecture in primary oral malignant melanoma. We sought to determine this by the use of periodic acid-Schiff (PAS) stain, endothelial markers (CD34, CD105) and laminin, and by transmission electron microscopy in two cases. The results demonstrated that endothelium-lined vessels dominated the tumor microvasculature and these stained positively for PAS, laminin, and endothelial markers. Mosaic and tumor-lined vessels were infrequently encountered. Most PAS-positive patterned networks and loops ultrastructurally represented intratumor microhemorrhages that probably arose secondary to tumor vessel leakiness. Vascular channels of the vasculogenic mimicry type were rare. They stained for laminin but not for endothelial markers.